Influência da inclusão do grupamento salicilato na atividade antifúngica de um sal imidazólico - Oliveira, Thayse Viana de (2013)
Imidazolium Ionic Liquids (ILs) are organic salts with recognized biological activity over microorganisms. In this work, an IL presenting a salicilato group as anion (C16MImC7H6O3) was tested as for its antifungal activity against dermatophytes, filamentous fungi known to cause cutaneous mycoses (dermatophytosis); and Candida non-albicans specie, a type of yeast considered to be opportunistic and emergent. The minimum inhibitory concentration MIC of the substance was determined using in vitro susceptibility testing, recommended by the CLSI. It was found that the inclusion of this group with known anti-inflammatory activity does not affect the antifungal activity of IL.